Short article: Negative small-bowel cross-sectional imaging does not exclude capsule retention in high-risk patients. Issue 8 (August 2016) - Rondonotti, Emanuele; Soncini, Marco; Girelli, Carlo M.; Russo, Antonio; de Franchis, Roberto
Abstract : Background and aims: Both Agile patency capsule (PC) and small-bowel cross-sectional imaging (SBCSI) techniques have been used to assess small-bowel patency in patients at high risk of capsule retention. The present study aimed to compare capsule retention rates in high-risk patients with negative PC or SBCSI. Materials and methods: Between January 2011 and December 2013, consecutive patients undergoing small-bowel capsule endoscopy (SBCE) in the Lombardia region were prospectively entered into a dedicated registry. They were classified as being at high or low risk of capsule retention by the local investigator according to predefined clinical criteria. High-risk patients underwent either PC or SBCSI depending on local expertise and availability; those who tested negative underwent SBCE. Results: Out of 3117 patients (male/female: 1667/1450, mean age: 63.1±17.7), 2942 (94.4%) were classified as being at low risk and 175 (5.6%) were classified as being at high risk for capsule retention. Among 175 high-risk patients, 151 (86.3%) had negative PC and 24 (13.7%) had negative SBCSI: capsule retention occurred in two patients with negative SBCSI (8.3%) and in one patient (0.7%) with negative PC ( P =0.049). The capsule retention rates in high-risk patients with negative PC and in low-risk patients (20/2942; 0.7%) were comparable ( P =1.0). Conclusion: The capsule retention rate is similar in low-risk and negative PC high-risk patients. Conversely, high-risk patients with negative SBCSI have a significantly higher capsule retention rate. Our data suggest that in high-risk patients, negative SBCSI examination is not reassuring and, when SBCE is indicated, PC should be performed. Abstract : Supplemental Digital Content is available in the text.